A survey on the use of pit and fissure sealants by general practitioners in four Municipalities in Metro Manila namely Manila Mandaluyong, Quezon City and Pasay City - Ludovice, Angelica S.
Pit and fissure sealant has been well-documented as a caries preventive measure since it was first introduced. However, there is a popular belief which is strengthened by written reports that its use is very low in both public and private dental practices. The sample population of 20% from each municipality were randomly chosen from the list of registered members of the following PDA Dental Chapters: Mandaluyong, Manila, Quezon City, Pasay City. A questionnaire was mailed to each respondent and follow-up thru telephone was made. Personal interviews were done in cases where the respondents failed to reply within 2 weeks after the mailing of the questionnaire. The survey revealed that 72.4% of the dentists use pit and fissure sealant as against 27.6% who do not use it. This is contrary to popular belief and written report. It is also revealed that for the four municipalities, location of practice does not influence the use of pit and fissure sealants.